Comparative Analysis of Undue Influence as a Basis for Contract Annulment: Comparison Indonesia and Malaysia - Fidhayanti, Dwi; Umam, Khairul; Hanafi, Hanira (Universitas Brawijaya, 2025)
This research offers novelty by conducting a comparative analysis of the application of the doctrine of undue influence in contract cancellation in Indonesia, particularly in the context of comparing different legal systems. Previous study such as those conducted by Ariyanto (2023), revealed that Indonesia lacks a clear legal framework regarding undue influence in contract cancellation. Meanwhile, Azam (2020) highlighted that the doctrine in consumer financing cases in Indonesia limits contractual freedom. This study compares the application of the doctrine of undue influence as a basis for contract cancellation in Indonesia and Malaysia, aiming to formulate an ideal model for Indonesia inspired by the application in Malaysia. The research method employs normative legal research method with a comparative legal approach. Legal materials are collected through extensive library research and analyzed using systematic and grammatical legal interpretation methodology. The novelty of this study lies in its in-depth comparison of the application of this doctrine in Indonesia and Malaysia, focusing on significant similarities between two countries, influencing how the harmed party seek cancellation. Indonesia has the opportunity to adopt Malaysia’s approach, which encourages judges to offer alternative solution and conduct deeper psychological analysis. This research may inspire ideas to explore the application of the doctrine of undue influence in the countries with different legal systems, such as those following common law or civil law systems.